Results and lessons from the Spironolactone To Prevent Cardiovascular Events in Early Stage Chronic Kidney Disease (STOP-CKD) randomised controlled trial - Ng, Khai P (BMJ Open, 2016)
OBJECTIVES: To determine whether low-dose spironolactone can safely lower arterial stiffness in patients with chronic kidney disease stage 3 in the primary care setting. DESIGN: A multicentre, prospective, randomised, placebo-controlled, double-blinded study. SETTING: 11 primary care centres in South Birmingham, England. PARTICIPANTS: Adult patients with stage 3 chronic kidney disease. Main exclusion criteria were diagnosis of diabetes mellitus, chronic heart failure, atrial fibrillation, severe hypertension, systolic blood pressure <120 mm Hg or baseline serum potassium ≥5 mmol/L. INTERVENTION: Eligible participants were randomised to receive either spironolactone 25 mg once daily, or matching placebo for an intended period of 40 weeks. OUTCOME MEASURES: The primary end point was the change in arterial stiffness as measured by pulse wave velocity. Secondary outcome measures included the rate of hyperkalaemia, deterioration of renal function, barriers to participation and expected recruitment rates to a potential future hard end point study. RESULTS: From the 11 practices serving a population of 112 462, there were 1598 (1.4%) patients identified as being eligible and were invited to participate. Of these, 134 (8.4%) attended the screening visit of which only 16 (1.0%) were eligible for randomisation. The main reasons for exclusion were low systolic blood pressure (<120 mm Hg: 40 patients) and high estimated glomerular filtration rate (≥60 mL/min/1.73 m(2): 38 patients). The trial was considered unfeasible and was terminated early. CONCLUSIONS: We highlight some of the challenges in undertaking research in primary care including patient participation in trials. This study not only challenged our preconceptions, but also provided important learning for future research in this large and important group of patients. TRIAL REGISTRATION NUMBER: ISRCTN80658312.